2013
DOI: 10.1371/journal.pone.0076599
|View full text |Cite
|
Sign up to set email alerts
|

Floating Ice-Algal Aggregates below Melting Arctic Sea Ice

Abstract: During two consecutive cruises to the Eastern Central Arctic in late summer 2012, we observed floating algal aggregates in the melt-water layer below and between melting ice floes of first-year pack ice. The macroscopic (1-15 cm in diameter) aggregates had a mucous consistency and were dominated by typical ice-associated pennate diatoms embedded within the mucous matrix. Aggregates maintained buoyancy and accumulated just above a strong pycnocline that separated meltwater and seawater layers. We were able, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 60 publications
6
90
3
1
Order By: Relevance
“…One possible explanation is that the INPs were associated with melting sea ice. Materials such as algal aggregates, sea ice diatoms, and extracellular polymeric substances can be released into the ocean upon sea ice melting (Assmy et al, 2013;Boetius et al, 2015;Fernández-Méndez et al, 2014) and might be potential sources of the INPs observed in this study. Also interesting, a strong positive correlation was observed between salinity and bacterial abundance (R = 0.76, p = 0.039).…”
Section: Inps In the Microlayer And Bulk Seawatermentioning
confidence: 90%
“…One possible explanation is that the INPs were associated with melting sea ice. Materials such as algal aggregates, sea ice diatoms, and extracellular polymeric substances can be released into the ocean upon sea ice melting (Assmy et al, 2013;Boetius et al, 2015;Fernández-Méndez et al, 2014) and might be potential sources of the INPs observed in this study. Also interesting, a strong positive correlation was observed between salinity and bacterial abundance (R = 0.76, p = 0.039).…”
Section: Inps In the Microlayer And Bulk Seawatermentioning
confidence: 90%
“…Primary production in the AO can comprise significant fractions that derive from ice algae (e.g., Tedesco et al, 2010Tedesco et al, , 2012Leu et al, 2015). During the Arctic melt season, floating ice algae aggregates likely play an important ecological role in an otherwise impoverished near-surface sea ice environment (Boetius et al, 2013;Assmy et al, 2014). The timing of phytoplankton and ice algae blooms as well as the biochemical composition is different.…”
Section: Confines and Limitationsmentioning
confidence: 99%
“…25 producers. Taxonomic assessment of the diatom assemblage within several algal aggregates from Resolute Bay in the Canadian Arctic revealed a distinctive flora, characteristic of sea ice [26][27][28] . Thus, the three most abundant species were Navicula pelagica (ca.…”
mentioning
confidence: 99%